2020
DOI: 10.3390/ijerph17176172
|View full text |Cite
|
Sign up to set email alerts
|

Validation of SEPI in German—A German Translation of the Sun Exposure and Protection Index

Abstract: The Sun Exposure and Protection Index (SEPI) is a brief instrument for scoring of sun exposure habits and propensity to increase sun protection, previously validated in English and in Swedish, as well as in two different outdoor sun intensity environments (Australia and Northern Europe). The aim of the present study was to study reliability and validity of a German translated version of the SEPI to be used in German-speaking populations. Data was collected at University of Flensburg and at Hamburg University o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 44 publications
(48 reference statements)
4
21
1
3
Order By: Relevance
“…Limitations of this study were the moderate sample size, a high proportion of nonresponders (31.6%), and a substantial number of lost-to-follow-up (24 participants, 14.0%). However, these numbers were also seen in the previous validation studies of the SEPI and were anticipated on in this study's sample size calculation [13,17]. One of the studies suggested using a more active recruitment strategy, which was done in the present study, but this did not lead to a higher response rate.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Limitations of this study were the moderate sample size, a high proportion of nonresponders (31.6%), and a substantial number of lost-to-follow-up (24 participants, 14.0%). However, these numbers were also seen in the previous validation studies of the SEPI and were anticipated on in this study's sample size calculation [13,17]. One of the studies suggested using a more active recruitment strategy, which was done in the present study, but this did not lead to a higher response rate.…”
Section: Discussionsupporting
confidence: 51%
“…The present study was carried out in a broad patient population that closely resembles the target population of the SEPI, which is one of the strengths of this study. Since the previous studies validating the SEPI included only students or students and primary health care patients, this study also gives new insights into the validity of the SEPI among primary health care patients and dermatologic patients [13, 17]. Moreover, the population in this study consists of a broad age range and diversity regarding educational level and work situation, which improves the generalizability of the results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To the best of our knowledge, however, we are not aware of any questionnaire or single item that standardizes tanning behavior and records it in an equally brief manner. Since the reliability of measuring solar UVR exposure in our study has to be critically discussed, future studies should use validated questionnaires for measurement, such as the recently published validated “ Sun Exposure and Protection Index ” [ 31 ]. The major strength of our study is the comprehensive literature search and the content analysis of questionnaires used in already published studies.…”
Section: Discussionmentioning
confidence: 99%
“…To provide reliable data on exposure as well as behavior and knowledge, validated questionnaires are needed. While the “ Sun Exposure and Protection Index ” (SEPI) [ 31 ], which is a validated questionnaire for the assessment of solar UVR exposure and sun protection behavior has recently become available in German, a questionnaire for assessing the level of knowledge is still missing. As Day et al [ 32 – 34 ] emphasize, differences in the measurement of knowledge should be avoided to facilitate the comparison of findings between studies.…”
Section: Introductionmentioning
confidence: 99%